2009
DOI: 10.1177/0040517509349782
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Some Comfort-related Properties of Socks of Different Fiber Types

Abstract: Socks need to perform better in comfort properties than other garments, as less air circulation occurs in socks in shoes than in garments on other parts of the body. In this paper, we studied the comfort properties of socks made from new fibers, such as modal, micro modal, bamboo, soybean, and chitosan. In order to compare their properties with conventional fibers such as cotton and viscose, these fibers were also included in the study. Water vapor transfer, air permeability, wicking, wetting and heat transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
61
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 18 publications
(29 reference statements)
6
61
1
Order By: Relevance
“…It is observed that cotton fabrics take lower values compared to other fabrics. Based on the findings of Cimilli et al (2009), who reported that the swelling of cotton fibers might have narrowed the gaps between the fibers and yarns, and consequently made it difficult for the capillary water transfer. Besides, as pointed out in Bivainytė and Mikučionienė (2011) study, cotton is characterized by high absorption levels, and cotton fabrics hold absorbed water in their structure and transferred it slowly.…”
Section: Vertical Wickingmentioning
confidence: 99%
See 1 more Smart Citation
“…It is observed that cotton fabrics take lower values compared to other fabrics. Based on the findings of Cimilli et al (2009), who reported that the swelling of cotton fibers might have narrowed the gaps between the fibers and yarns, and consequently made it difficult for the capillary water transfer. Besides, as pointed out in Bivainytė and Mikučionienė (2011) study, cotton is characterized by high absorption levels, and cotton fabrics hold absorbed water in their structure and transferred it slowly.…”
Section: Vertical Wickingmentioning
confidence: 99%
“…According to the study results, it was seen that water vapor permeability decreased as the polyester amount increased in polyester/viscose and polyester/cotton blends. In the study of Cimilli, Nergis, Candan, and Özdemir (2009), the comfort properties of socks produced from new fibers such as modal, micro-modal, bamboo, soybean, and chitosan were examined. In addition, conventional fibers such as cotton and viscose are examined in the study and compared with other fibers.…”
Section: Introductionmentioning
confidence: 99%
“…According to a literature survey, fabric thickness and porosity significantly affect the transfer wicking ratio. 19,20 However, as shown in Table 1, fabric K-X series did show similarly thicknesses and weights. Therefore, the transfer wicking ratio was mainly related with the components of blending yarn A.…”
Section: Transfer Wicking Test Resultsmentioning
confidence: 67%
“…In the study of Cimilli et al [26] on the comfort properties of socks made up of different kinds of fibres, it was reported that the drying time was affected by the amount of initial liquid absorption which is connected to the fibre type. Çil et al [27] have concluded that the most significant parameter is the yarn count regardless of the initial water content for the drying of cotton/acrylic blended knitted fabrics.…”
Section: Introductionmentioning
confidence: 99%